Modulação tecnológica e biológica da Curcumina por meio do revestimento de nanocápsulas poliméricas - Santos, Renata Bem dos (2022)
Curcumin (CCM) is a compound extracted from Curcuma longa, which has therapeutic potential and proven efficacy for the treatment of various diseases. However, due to its physicochemical characteristics, it has some limitations, such as low aqueous solubility and consequent low bioavailability, in addition to suffering photodegradation and chemical degradation by pH changes. To circumvent this problem, nanocarriers are used, which may have different surface characteristics, depending on the objective of the study. One of the essential steps in the development of new formulations is the physicochemical and biological characterization of these systems. Increasingly, population pharmacokinetic modeling (popPK) has been used to identify intra and inter-individual variability that interferes with the safety and efficacy of the drug. Considering the need for an effective delivery system and an adequate characterization of it, we developed nanocapsules (NC) loaded with CCM and in the absence of the compound (NC-B), with anionic (P80 and PEG) and cationic (CS and EUD) coatings, characterized in physicochemical and morphological terms, through analysis of particle size, zeta potential, pH, assay and encapsulation efficiency, AFM, FTIR, DSC, XRD, and in vitro release profile, in addition to the evaluation of antimalarial activity ( NC and NC-B), antiviral and antitumor (NC-B) in vitro. We also performed a pharmacodynamic (PD) evaluation in an apomorphine-induced stereotyped model and in vivo pharmacokinetics (PK) of PEG and CS NC in male Wistar rats, followed by a non-compartmental (NCA) and population PK (popPK) study. Our results provide a very broad and adequate characterization of the proposed delivery systems, with good CCM encapsulation capacity and a controlled release, with a biexponential profile, regardless of the type of coating used. NC was able to improve the effects of CCM in an apomorphine-induced stereotypy model, especially NCCS. In addition, the results of PK NCA demonstrated the influence of nanoencapsulation on both Cl and Vd. NC popPK was best described by a two-compartment model with linear elimination. This set of results allows us a broad view of the characteristics of nanoencapsulated CCM and its effects in vitro and in vivo.